H19 Noncoding RNA, an Independent Prognostic Factor, Regulates Essential Rb-E2F and CDK8-β-Catenin Signaling in Colorectal Cancer - Ohtsuka, Masahisa; Ling, Hui; Ivan, Cristina; Pichler, Martin; Matsushita, Daisuke; Goblirsch, Matthew; Stiegelbauer, Verena; Shigeyasu, Kunitoshi; Zhang, Xinna; Chen, Meng; Vidhu, Fnu; Bartholomeusz, Geoffrey A; et al. (EBioMedicine, 2016)
The clinical significance of long noncoding RNAs (lncRNAs) in colorectal cancer (CRC) remains largely unexplored. Here, we analyzed a large panel of lncRNA candidates with The Cancer Genome Atlas (TCGA) CRC dataset, and identified H19 as the most significant lncRNA associated with CRC patient survival. We further validated such association in two independent CRC cohorts. H19 silencing blocked G1-S transition, reduced cell proliferation, and inhibited cell migration. We profiled gene expression changes to gain mechanism insight of H19 function. Transcriptome data analysis revealed not only previously identified mechanisms such as Let-7 regulation by H19, but also RB1-E2F1 function and β-catenin activity as essential upstream regulators mediating H19 function. Our experimental data showed that H19 affects phosphorylation of RB1 protein by regulating gene expression of CDK4 and CCND1. We further demonstrated that reduced CDK8 expression underlies changes of β-catenin activity, and identified that H19 interacts with macroH2A, an essential regulator of CDK8 gene transcription. However, the relevance of H19-macroH2A interaction in CDK8 regulation remains to be experimentally determined. We further explored the clinical relevance of above mechanisms in clinical samples, and showed that combined analysis of H19 with its targets improved prognostic value of H19 in CRC.
Keywords: signální transdukce; Signal Transduction; retinoblastomový protein; Retinoblastoma Protein; regulace genové exprese u nádorů; Humans; E2F; analýza přežití; beta-katenin; RNA, Long Noncoding; RNA dlouhá nekódující; genové regulační sítě; Gene Regulatory Networks; lidé; H19; zvířata; myši; CDK8; β-Catenin; Survival Analysis; Mice; transkripční faktory E2F; RB1; Cyclin-Dependent Kinase 8; kolorektální nádory; cyklin-dependentní kinasa 8; Colorectal cancer; prognóza; stanovení celkové genové exprese; transkriptom; RNA Interference; beta Catenin; nádorové buněčné linie; Transcriptome; databáze nukleových kyselin; Animals; Cell Line, Tumor; Databases, Nucleic Acid; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; RNA interference; E2F Transcription Factors; Prognosis; Colorectal Neoplasms